SIKHOTE ALIN AS A POSSIBLE PROVINCE OF HYDROTHERMAL SEDIMENTARY GOLD, SILVER, PGE, TIN, ZINC, LEAD, AND TUNGSTEN DEPOSITS - Kazachenko V.T.; Miroshnichenko N.V.; Perevoznikova E.V.; Karabtsov A.A. (My University, 2006)
The Triassic–Jurassic carbonaceous sequence of Sikhote Alin contains metalliferous sediments composed of siliceous–rhodochrosite rocks and their metamorphosed analogues (mainly, manganese silicates and aluminosilicates), pyrophanite-bearing siliceous rocks (hereafter, brown cherts), tin–iron ores, ilmenite–biotite–feldspar rocks, and itabirites. Metalliferous sediments of all types have high contents of Au, Ag, and PGE.
Keywords: Sikhote Alin; Мезозой::Триасовая; Мезозой::Юрская